Systematic Characterization of High-Power Short-Duration Ablation: Insight From an Advanced Virtual Model - Petras, Argyrios; Moreno Weidmann, Zoraida; Leoni, Massimiliano; Gerardo-Giorda, Luca; Guerra, Jose M. (Frontiers in Medical Technology, 2021)
Background. High-Power Short-Duration (HPSD) recently emerged as a new approach to radiofrequency (RF) catheter ablation. However, basic and clinical data supporting its effectiveness and safety is still scarce. Objective. We aim to characterize HPSD with an advanced virtual model, able to assess lesion dimensions and complications in multiple conditions and compare it to standard protocols. Methods. We evaluate, on both atrium and ventricle, three HPSD protocols (70W/8s, 80W/6s and 90W/4s) through a realistic 3D computational model of power-controlled RF ablation, varying catheter tip design (spherical/cylindrical), contact force, blood flow and saline irrigation. Lesions are defined by the 50oC isotherm contour. Ablations are deemed safe or complicated by pop (tissue temperature >97ºC) or charring (blood temperature >80ºC). We compared HPSD with standards protocols (30-40W/30s). We analyzed the effect of a second HPSD application. Results. We simulated 432 applications. Most (79%) associated a complication, especially in the atrium. The three HPSD protocols performed similarly in the atrium, while 90W/4s appeared the safest in the ventricle. Low irrigation rate led frequently to charring (72%). HPSD lesions were 40-60% shallower and smaller in volume compared to standards, although featuring similar width. A second HPSD application increased lesions to a size comparable to standards. Conclusion. HPSD lesions are smaller in volume and more superficial than standards but comparable in width, which can be advantageous in the atrium. A second application can produce lesions similar to standards in a shorter time. Despite its narrow safety margin, HPSD seems a valuable new clinical approach.